Efektivitas Perlindungan Hukum Terhadap Hak Dan Kewajiban Masyarakat Hukum Adat Terhadap Hak Ulayat Suku Nafri Distik Abepura Kota Jayapura - Reumy, Ludia Jemima I. R. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study reveals that customary land is land that is controlled collectively by members of the customary law community, where the management is carried out by the customary leader (Customary Head) and its use is intended for both members of the customary law community concerned and outsiders. To be able to state that a customary right in a certain place still exists, there are three main elements that must be fulfilled, namely the community element, the territorial element and the element of the relationship between the customary law community and its territory. There are two problems in this study regarding customary land ownership based on the UUPA and legal protection of the rights and obligations of customary law communities, as well as the concept and forms of government roles in guaranteeing the rights and obligations of customary law communities and the protection of land control rights of customary law communities in Indonesia. This study uses an empirical legal research method, namely a legal research method that analyzes the application of law in reality towards individual community groups, customary institutions in society, and emphasizes the behavior of individuals or communities, organizations or legal institutions in relation to seeing and examining how the law works in society. The results of this study state that the role of the government in protecting the rights of customary law communities is very important considering the inhibiting factors that become obstacles to consideration in protecting the rights and obligations of customary law communities regarding customary rights which are the same inheritance objects as the obligation not to violate the rights of control and ownership of customary land of customary law communities, and also at the same time have the obligation to protect in the sense of preventing and taking action against violations.